Sokrates i Diogenes – dwie antyczne metody edukacji etycznej - Piotrowski, Paweł (Studia Edukacyjne, 2025)
The ancient Greek philosopher, Diogenes of Sinope was one of most prominent representatives of the Cynic philosophical school, one of principal developmental lines of Socratic philosophy. The most recognizable features of Socratic philosophy include moralism, ethical intellectualism, and heuristics as the method of philosophical investigation and teaching. Diogenes agreed entirely with Socratic moralism but he had his own interpretation of ethical intellectualism and his own method of teaching ethics. He followed it by intellectually (and sometimes customs-related) provocative actions and statements, so-called chreia. The article compares some assumptions of the disparate didactic methods used by Socrates and Diogenes. This comparison is made mainly in a context of ethical education both the methods were intended for.